ON THE ISSUE OF PALEOHYDROGRAPHY AND THE LOCALIZATION OF OASISS IN THE LOWER SYRDARYA IN THE EARLY MIDDLE AGES - Berdiev, Jamiet Turemuratovich (SCIENCE and SOCIETY, 2026)
The article examines the paleohydrographic transformations and settlement topography of the Lower Syr Darya oases (Dzhetyasar culture) in the early Middle Ages (6th–9th centuries) using interdisciplinary methods. The dynamics of the hydrographic network in the Syr Darya delta and its influence on the economic adaptation of the oasis civilization are analyzed. It is established that the transformation of water resources directly affected the localization of micro-oases and regional demographic processes.